2013
DOI: 10.1007/s40265-013-0112-5
|View full text |Cite
|
Sign up to set email alerts
|

11β-HSD1 Inhibitors for the Treatment of Type 2 Diabetes and Cardiovascular Disease

Abstract: Inhibition of the enzyme 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) has been proposed as a novel therapeutic target for the treatment of type 2 diabetes mellitus. Over 170 new compounds targeting 11β-HSD1 have been developed. This article reviews the current published literature on compounds that have reached phase II clinical trials in patients with type 2 diabetes, and summarises the preclinical evidence that such agents may be useful for associated conditions, including peripheral vascular disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 63 publications
1
59
0
4
Order By: Relevance
“…It remains an open question as to whether there might be utility for other indications [25, 26]. For example, given that mice lacking 11-HSD1 do not develop signs of Cushing’s syndrome when administered glucocorticoids [12] and that, rarely, humans with low 11-HSD1 activity also have mild phenotypes when they develop Cushing’s syndrome, it has been suggested that pharmacologic inhibition of 11-HSD1 might be used as adjunctive treatment for Cushing’s syndrome [27].…”
Section: Functional Roles Of 11-hsd1mentioning
confidence: 99%
“…It remains an open question as to whether there might be utility for other indications [25, 26]. For example, given that mice lacking 11-HSD1 do not develop signs of Cushing’s syndrome when administered glucocorticoids [12] and that, rarely, humans with low 11-HSD1 activity also have mild phenotypes when they develop Cushing’s syndrome, it has been suggested that pharmacologic inhibition of 11-HSD1 might be used as adjunctive treatment for Cushing’s syndrome [27].…”
Section: Functional Roles Of 11-hsd1mentioning
confidence: 99%
“…• Ces essais démontrent l'intérêt thé-rapeutique potentiel des inhibiteurs sélectifs de la 11βHSD1 dans la prise en charge de l'obésité compliquée d'un DT2 ou d'une HTA et, d'une façon plus large, dans le traitement du syndrome métabolique [32,33]. Cependant, globalement, les résultats cliniques ont été jugés insuffisants par comparaison à ceux obtenus avec d'autres classes de médicaments déjà disponibles, en particulier face à l'émergence des nouveaux antidiabétiques oraux représentés par les inhibiteurs de la dipeptidyl peptidase-4 (gliptines) et les inhibiteurs des co-transporteurs sodium-glucose de type 2 (gliflozines) [34].…”
Section: Dossier Thématiqueunclassified
“…De nouveaux inhibiteurs de la 11βHSD1 sont toujours en développement, pour la plupart à une phase encore relativement précoce [3,26,32,45]. Ceci démontre qu'il persiste un intérêt pour cette approche thérapeutique qui consiste à inhiber l'activité de cette enzyme.…”
Section: Nouveaux Inhibiteurs De La 11βhsd1 En Développementunclassified
“…В противопо-ложность этому, гиперэкспрессия 11b-HSD1 в жировой ткани приводила к ожирению и нарушению толерант-ности к глюкозе. Еще большая экспрессия 11b-HSD1 в печени приводила к гипертензии и дислипидемии в дополнение к инсулиновой резистентности [8].…”
Section: ингибиторы 11-бета-гидроксистероиддегидрогеназы 1-го типа (1unclassified
“…Клини-ческие исследования ингибиторов 11b-HSD1 продол-жаются, предполагается, что они смогут снизить риск множественных осложнений СД, включая сердечно-со-судистые и когнитивные осложнения [8].…”
Section: ингибиторы 11-бета-гидроксистероиддегидрогеназы 1-го типа (1unclassified